Planning the Development of Special Interest Tourism in the Geopark Area of Mount Batur, Kintamani, Bangli Regency - I Wayan Juli Arimbawa (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
In Bali, one of the tourist attraction areas that has potential and opportunities for geopark development is the Kintamani area. Hundreds or even thousands of tourists have visited to see the natural beauty around Mount Batur, Kintamani. The problems in this research include (1) Why is the Mount Batur Geopark in Kintamani, Bangli Regency categorized as a special interest tourism destination?; and (2) What is the perception of tourists regarding the Mount Batur Geopark area in Kintamani, Bangli Regency as special interest tourism? This research uses a qualitative research type and approach. The reason for using a qualitative research design is because essentially it is observing people in their living environment, which in this case is the community around the Mount Batur Geopark area in Kintamani, Bangli Regency. The data analysis technique used was qualitative data analysis techniques with an interactive model from Miles and Huberman. The research results show (1) The reason the Mount Batur Geopark in Kintamani, Bangli Regency is categorized as a special interest tourism destination is because the Mount Batur Geopark has 3 (three) tourism beauties which include geodiversity, biodiversity and culture. Tourists really like different and unique views compared to natural attractions in other areas; and (2) Tourist perceptions of the Mount Batur Geopark area in Kintamani, Bangli Regency as special interest tourism are very good, while tourists' perceptions of amenities are less good. Keywords: Development, Planning, Special Interest, Tourism.